Hormonal therapy and thromboembolic disease - Barczyński, Bartłomiej; Kotarski, Jan (Menopause Review/Przegląd Menopauzalny, 2008)
One of the most serious adverse effects of oral contraceptive therapy and hormonal therapy (HT) is thromboembolic disease. According to the literature use of oral oestrogen-based HT causes a 2-3-fold increased relative risk for thromboembolic events in perimenopausal women. The risk of thromboembolic complications is dependent on the type of oestrogen and progestogen. The number of unfavourable adverse events may be effectively reduced by changing the route of HT administration (from oral to transdermal), decreasing the dose of oestrogen component and/or changing the type of progestogen component. Implementation of hormonal treatment should in all cases be individualized and based on the patient’s needs and expectations as well as general health status.